The Impact of Using Problem-Solving Strategy on Metacognition Thinking and Motivation towards Learning Mathematics among Fourth Basic Grade Students in Jordan - Abdul Rahman, Raidah Hassan Nimr; Abu Sneineh, Odeh AbdelGawad (Journal of Curriculum and Teaching Methodology, 2023)
The current study aimed to identify the effectiveness of using the problem-solving strategy on metacognitive thinking and the motivation towards learning mathematics among the fourth grade students in Jordan. To achieve the goals of the study, the researcher developed a problem-solving test and a motivation scale. Then the validity and reliability of these instruments were confirmed. The study sample was chosen from the fourth grade students from Omayr Bin Abi Waqqas Mixed School affiliated to Directorate of Education in the Qasaba Amman District. The study adopted the quasi-experimental mode of inquiry. Therefore, two classes were randomly selected from the fourth grade classes; the sample included (60) male and female students. The results of the first question revealed the superiority in favor of the experimental group, which utilized the problem-solving strategy in developing metacognitive thinking among fourth-grade students in the subject of mathematics, compared to the usual method of teaching. Moreover, the results of the second question showed superiority in favor of the experimental group, which used the problem-solving strategy in developing motivation towards learning mathematics among fourth grade students, compared to the usual method of teaching. The study recommended the Ministry of Education should include problem-solving strategies in the mathematics curriculum for fourth-grade students to help them develop their metacognitive thinking and motivate them to learn mathematics.